CGIAR Platform for Big Data in Agriculture - Plan of Work and Budget 2021 - CGIAR Platform for Big Data in Agriculture (CGIAR Platform for Big Data in Agriculture, 2021)
The CGIAR Platform for Big Data in Agriculture is a cross-cutting program of the global CGIAR consortium of non-profit research institutes looking into virtually every aspect of food security spanning: genomics, breeding, agroecology, climate science, and the socioeconomic drivers and context of food systems change. The Platform tends to data standards and data sharing, digital innovation strategy and technology transfer, and research into the intersection of digital technologies and agricultural development in emerging regions.